Effectiveness of non-surgical periodontal therapy on glycemic control of Type 2 diabetic patients with periodontitis in public primary care clinics, Kuantan, Pahang - Md Aris, Mohd Aznan; Tin, Myo Han; Ismail, Razida; Yaacob, Munirah; Osman, Iskandar Firzada; Sidek, Sorayah; Thuraiapprah, Mahendran; Abdullah, Fa’iza; Hari, Padmini; Than, Tun Sein; Saub, Roslan (2017)
Introduction : Diabetes mellitus (DM) patients who achieved treatment target HbA1c ≤ 6.5% was 17.4% in Malaysia1,2. Prevalence of DM patients with periodontitis co-morbidity (DM-P) in Malaysia was 53.3%3. Effectiveness of non-surgical periodontal therapy (NSPT) on glycemic control of DM-P patients has been reported in previous studies4,5,6 Objective : To evaluate the effectiveness of NSPT on achieving target HbA1c ≤ 6.5% in type-2DM patients with periodontitis (T2DM-P) from public primary care clinics